2021
DOI: 10.5334/jbsr.2483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changing the Reporting System from Decentralized/Modality-Based to Centralized/Subspecialized Radiology on Radiologists, Radiologic Technicians and Referring Physicians of a Multi-Center Radiology Network

Abstract: Objectives: To determine the effects of reorganizing a radiology institute from decentralized/modality-based to centralized/subspecialized radiology on radiologists, radiologic technicians, and referring physicians at a multi-center radiology network. Material and Methods: In 2017/2018 our multi-center radiology network was changed from decentralized/modality-based to centralized/subspecialized reporting. A survey was conducted among radiologists, technicians and two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…These findings are in line with a previous study from Miller et al [ 8 ] where a dedicated second reading of hernia scans by a radiologist led to a significant increase in accuracy compared to the baseline radiology reports (accuracy increased from 35 to 79%). Other studies have shown an increase in perceived report quality and decrease in interpretive discrepancies with subspecialized reporting [ 27 , 28 ]. Subspecialized reporting can yield significant clinical advantages, particularly in instances involving small and clinically occult hernias.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with a previous study from Miller et al [ 8 ] where a dedicated second reading of hernia scans by a radiologist led to a significant increase in accuracy compared to the baseline radiology reports (accuracy increased from 35 to 79%). Other studies have shown an increase in perceived report quality and decrease in interpretive discrepancies with subspecialized reporting [ 27 , 28 ]. Subspecialized reporting can yield significant clinical advantages, particularly in instances involving small and clinically occult hernias.…”
Section: Discussionmentioning
confidence: 99%